Analysis of the Potential of Sport Tourism in Nglanggeran Tourism Village Post Covid 19 Pandemic - Miya Kurniawati; Soewanto Jaya; Hongie Swansyah (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: The objectives of this study are (1) to determine the mapping of sports tourism potential in Nglanggeran Tourism Village after the Covid-19 pandemic, (2) to determine the inhibiting and supporting factors of sports tourism potential in Nglanggeran Tourism Village after the Covid-19 pandemic. Methodology: The research used qualitative descriptive. The data sources used are primary data and secondary data, using data collection methods, namely observation, interviews, literature studies and documentation. The informants of this study are: Nglanggeran Tourism Village Manager, Village Government, Gunungkidul Tourism Office, Gunungkidul Youth and Sports Office. The data analysis technique uses MSPDM (Marketability, Sustainability, Participatory, and Disaster Mitigation) analysis. The data validity technique uses triangulation techniques. Main Findings: The results of the study show that; (1) Marketing of Nglanggeran Tourism Village has been good in following technological developments, (2) Sustainability of tourism in a growing status, There needs to be a collaborative movement and cooperation with stakeholders, (3) Community participation and involvement are quite active in providing tourism services for visitors, (4) Disaster mitigation is still not optimal and there is no disaster management. The potential for mapping sports tourism that can be held includes Run Heritage, Geoheritage Cross Country, Marathon Geopark, Mountain Bike Nglanggeran, Gymnastics and Yoga, Tracking, Healthy Walking, Jogging Track. Novelty/Originality of this study: Based on the research findings, policy recommendations are prepared that can be adopted by local governments and other stakeholders to support the development of sport tourism in Nglanggeran Tourism Village effectively and sustainably.